ETIKA GENERASI MILENIAL SEBAGAI PERWUJUDAN NILAI-NILAI PANCASILA (Jurnal Sosial Humaniora dan Pendidikan, 2023)
This study aims to provide an explanation and recommendations based on previous studies on the ethics of the millennial generation in the framework of realizing Pancasila. This research is a qualitative research using a literature review method from previous research and textbooks that are appropriate to the topic. The research data is in the form of primary and secondary data obtained by means of a literature review. Qualitative research data analysis uses the stages suggested by Miles & Hubberman (1992) consisting of data collection, data reduction, displaying the reduced data and drawing conclusions. The results of the study show that in general the millennial generation still has ethics in interacting with their environment, although there are several studies showing that the millennial generation is unethical in using social media